Case report: Solitary fibrous tumor of the kidney with a NAB2-STAT6 fusion gene - Ji, Wen-Tong; Hu, Yu; Wang, Yao (Frontiers in Oncology, 2022)
Background Solitary fibrous tumor (SFT) is a rare spindle cell neoplasm that mostly originates from the pleura, and accounts for only 2% of all soft tissue tumors. Moreover, the cases of SFT of the kidney are rarely reported. Here, we report a typical case of kidney SFT, which was consistent with other reported cases. This case further expands on existing diagnostic methods of SFT and explains the importance of STAT6 mutations in SFT. Case Summary We report a typical case of SFT of the kidney. A 34-year-old woman presented to the urinary surgery department after physical examinations were suggestive of a urologic neoplasm. Further relevant imaging investigations suggested a renal tumor with benign behaviors. The patient was diagnosed with a kidney tumor suspected to be SFT and underwent laparoscopic radical left nephrectomy. Postoperative pathological immunohistochemical tests showed positivity for Signal Transducer and Activator of Transcription 6(STAT6), CD-34, CD-99, and Bcl-2, thus confirming the diagnosis of SFT. Combined with the results of genetic testing of the patient, the tumor was indicated to carry NGFI-A-Binding protein 2(NAB2): exon 6—STAT6: exon 16 mutation sites, which confirmed our diagnosis. The patient recovered quickly without any clinical evidence of incomplete resection. She has been followed-up for more than a year and will continue to be reviewed every three months to observe the final outcomes. Conclusion Solitary fibrous tumor is difficult to differentiate from other renal tumors. CT imaging, STAT6 immunostaining and gene profiling are valid investigations to establish the diagnosis.